PENERAPAN MODEL PEMBELAJARAN INDEX CARD MATCH UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Iis Istianah; Piyantina Rukmini; Dede Hadiansah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research uses the classroom action research (CAR) method aimed at enhancing students' learning creativity and learning outcomes. One of the efforts made is to implement the Index Card Match learning model in science education. The research was conducted through four stages: planning, action, observation, and reflection. The study was conducted on 24 fifth-grade students of SDN 5 Juntikedokan. After implementing the Index Card Match learning model, there was an increase in students' learning creativity and learning outcomes, as evidenced by test results supported by observations of students' learning creativity. In the pre- cycle, the average score of students' learning outcomes was 60.00 with a completeness percentage of 41%, which increased to 66.00 in cycle I with a completeness percentage of 59%. In cycle II, it increased to 75.00 with a completeness percentage of 75%, and it met the achievement indicators in cycle III with an average score of 80.00 and a completeness percentage of 88%.